Perioperative Morbidity and Short-Term Surgical Outcomes Following Sacrospinous Ligament Fixation in Women with Advanced Uterovaginal Prolapse: A Prospective Observational Study - Dr Chandana M H, Dr Chandrashekar K, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background:-Advanced uterovaginal prolapse is a common pelvicfloor disorder requiring surgical correction in women with severe pelvic support defects. Vaginalhysterectomy combined with sacrospinous ligamentfixation (SSLF) has gained acceptance as aneffective vaginal reconstructive procedure thatrestores apical support while minimizing the risk of postoperative vaginal vault prolapse